PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA SEKTOR KESEHATAN DI BURSA EFEK INDONESIA - Ridwan (2023)
This study aims to analyze whether there is an influence between Liquidity, Solvency, and Profitability on Stock Returns which is carried out partially in health sector companies that are members of the Indonesia Stock Exchange in the period 2017 - 2021. There are 13 samples used, which were taken using the purposive sampling technique. Data type is secondary data in the form of financial reports obtained from the idx website. The analysis used by the researcher is multiple regression with the t test processed in the Eviews-12 application. The independent variables are Liquidity, Solvency, and Profitability with the dependent variable namely stock returns. The research results show that Liquidity, Solvability, and Profitability partially have no significant effect on stock returns.